Nyskapende radioestetikk og pragmatisk leilighets-arbeid – hørespillsjangeren i Inger Hagrups verk - Folkvord, Ingvild (Nordlit, 2012)
This article focuses on a frequently neglected part of the Norwegian author Inger Hagerup’s (1905-1985) work: her occupation with the popular genre of radio play. Based upon Ernst Cassirer’s dynamic approach to formative cultural work and expressive meaning, the article investigates two of Hagerup’s works produced for the Norwegian Broadcasting Corporation (NRK): Firstly her own radioplay Hilsen fra Katarina (1949), secondly her translation of Ingeborg Bachmann’s Der gute Gott von Manhattan (1957). Through a juxtaposition of the two, Hagerup’s own radio play stands out as an innovative contribution to the particular Norwegian development of this genre, and as a modern, far more experimental, work than her poems from the same period. Her translation of Bachmann’s work appears as surprisingly reductive with respect to the complexity of Bachmann’s original text. The article points out how the translation of Bachmann’s play to a Norwegian context can also be viewed as a cultural transfer highlighting different ideas of a popular genre during the first decades after World War II.